Hubungan Internal Karyawan sebagai Faktor Penentu Loyalitas dan Kinerja - Nadhirah Hamida; Helena Angelin; Erika Nor Aini; Haliza Laily Ningrum; Dewi Nuraini (Educational Journal, 2026)
Internal employee relations are a crucial aspect of organizational sustainability. Good interactions between employees and between employees and management can create a conducive work environment, increase loyalty, and encourage optimal performance. This article aims to examine the role of internal employee relations in improving loyalty and performance, as well as the factors that influence them. The method used is a literature review, reviewing various theories and previous research findings. The study results indicate that effective communication, trust, and teamwork are key to building strong internal relations. Therefore, organizations need to consider internal relationship management strategies to achieve their desired goals.